Institutional Review Board Use of Outside Experts: A National Survey. Issue 4 (31st October 2022) - Serpico, Kimberley; Rahimzadeh, Vasiliki; Gelinas, Luke; Hartsmith, Lauren; Lynch, Holly Fernandez; Anderson, Emily E.
Abstract: Background: Institutional review board (IRB) expertise is necessarily limited by maintaining a manageable board size. IRBs are therefore permitted by regulation to rely on outside experts for review. However, little is known about whether, when, why, and how IRBs use outside experts. Methods: We conducted a national survey of U.S. IRBs to characterize utilization of outside experts. Our study uses a descriptive, cross-sectional design to understand how IRBs engage with such experts and to identify areas where outside expertise is most frequently requested. Results: The survey response rate was 18.4%, with 55.4% of respondents reporting their institution's IRB uses outside experts. Nearly all respondents who reported using outside experts indicated they do so less than once a month, but occasionally each year (95%). The most common method of identifying an outside expert was securing a previously known subject matter expert (83.3%). Most frequently, respondents sought consultation for scientific expertise not held by current members (69.6%). Almost all respondents whose IRBs had used outside experts reported an overall positive impact on the IRB review process (91.5%). Conclusions: Just over half of the IRBs in our sample report use of outside experts; among them, outside experts were described as helpful, but their use was infrequent overall. Many IRBs report not relying on outside experts at all. This raises important questions about what type of engagement with outside experts should be viewed as optimal to promote the highest quality review. For example, few respondents sought assistance from a Community Advisory Board, which could address expertise gaps in community perspectives. Further exploration is needed to understand how to optimize IRB use of outside experts, including how to recognize when expertise is lacking, what barriers IRBs face in using outside experts, and perspectives on how outside expert review impacts IRB decision-making and review quality.